Reading site measurements and noting it on site drawing sheets - Temples of India Project Team (Jio Institute, 2024)
Ar. Mrunal Nidadacolu reading site measurements while Ar. Abhyuday Krishna is noting the same on-site drawing sheets, Neelkanth Group of Temples, Alwar district, Rajasthan. (Image courtesy: Ar. Ankita Peshin)